A stability result for the vibrations given by the standard linear model with thermoelasticity of type III. Issue 10 (27th July 2018) - Apalara, Tijani A.; Messaoudi, Salim A.; Al-Smail, Jamal H.
Abstract: The aim of this article is to establish the well-posedness as well as an exponential stability result for the standard linear solid vibrating systems of thermoelasticity type III. Numerical experiments using finite differences are given to confirm our analytical result.